PEMBELAJARAN TILAWAH AL-QUR’AN PADA SANTRI TPQ TADZKIRATUL ‘ULUM DI DESA WANGKELANG - Lathif, Mufti; Chikmah, Lailatul; Fauzah, Ma’rifatun; Rizquna, Via; Patrista, Titah Iffahaini; Sholikhah, Sevira Putri; Adinugraha, Hendri Hermawan (Universitas Methodist Indonesia, 2023)
This paper is the result of activities carried out by the author regarding the study of learning recitations of the Koran for TPQ Tadzkirotul 'Ulum students in Wangkelang Village, Moga District, Pemalang Regency. Writing is the result of the author's activities which are motivated by the importance of being a santri in mastering the learning of recitations of the Qur'an, therefore it can make it easier for students to understand the contents of the Qur'an and its meaning. This activity aims to socialize Al-Qur'an recitations which include steps for learning recitations of the Qur'an, methods, and objectives. The purpose of this activity is to foster a sense of love for the Koran by introducing students to how to read the Koran in a good, correct, and beautiful way.